Semantic congruence affects hippocampal response to repetition of visual associations. (September 2016) - McAndrews, Mary Pat; Girard, Todd A.; Wilkins, Leanne K.; McCormick, Cornelia
Abstract: Recent research has shown complementary engagement of the hippocampus and medial prefrontal cortex (mPFC) in encoding and retrieving associations based on pre-existing or experimentally-induced schemas, such that the latter supports schema-congruent information whereas the former is more engaged for incongruent or novel associations. Here, we attempted to explore some of the boundary conditions in the relative involvement of those structures in short-term memory for visual associations. The current literature is based primarily on intentional evaluation of schema-target congruence and on study-test paradigms with relatively long delays between learning and retrieval. We used a continuous recognition paradigm to investigate hippocampal and mPFC activation to first and second presentations of scene-object pairs as a function of semantic congruence between the elements (e.g., beach-seashell versus schoolyard-lamp). All items were identical at first and second presentation and the context scene, which was presented 500 ms prior to the appearance of the target object, was incidental to the task which required a recognition response to the central target only. Very short lags 2–8 intervening stimuli occurred between presentations. Encoding the targets with congruent contexts was associated with increased activation in visual cortical regions at initial presentation and faster response time at repetition, but we did not find enhanced activation in mPFC relative to incongruent stimuli at either presentation. We did observe enhanced activation in the right anterior hippocampus, as well as regions in visual and lateral temporal and frontal cortical regions, for the repetition of incongruent scene-object pairs. This pattern demonstrates rapid and incidental effects of schema processing in hippocampal, but not mPFC, engagement during continuous recognition. Highlights: Semantic congruence of object-scene pairs provides a schema for associative recognition. It enhanced reaction time and reduced hippocampal activation at target recognition. In contrast, hippocampal activation increased when recognizing incongruent targets. Schema effects occurred even when it was incidental and at very short repetition lags. However, medial prefrontal cortex was not engaged under these conditions.